Association between oxidative balance score and 10-year atherosclerotic cardiovascular disease risk: results from the NHANES database - Jin, Dekui; Lv, Tian; Chen, Shiqin; Chen, Yiqiao; Zhang, Chengying; Wang, Xiaoling; Li, Jie (Frontiers in Nutrition, 2024)
Introduction The oxidative balance score (OBS) is a holistic measure that represents the overall equilibrium between prooxidants and antioxidants in one’s diet and lifestyle. Little research has been conducted on the correlation between OBS and 10-year atherosclerotic cardiovascular disease risk (ASCVD). Therefore, the objective of this investigation was to examine the potential correlation between OBS and 10-year risk. Methods A total of 11,936 participants from the NHANES conducted between 2001 and 2016 were chosen for the study and their dietary and lifestyle factors were used to assess the OBS score. Logistic regression and restricted cubic splines (RCS) were employed in the cross-sectional study to evaluate the correlation between OBS and the 10-year ASCVD risk. The cohort study utilized Cox proportional hazards models and RCS to assess the correlation between OBS and all-causes and cardiovascular disease (CVD) mortality in individuals with high ASCVD risk. Results The cross-sectional study found that the OBS (OR = 0.94, 95% CI = 0.93–0.98), as well as the dietary OBS (OR = 0.96, 95% CI = 0.92–0.96) and lifestyle OBS (OR = 0.74, 95% CI = 0.69–0.79), were inversely associated with the 10-year ASCVD risk. A significant linear relationship was observed between OBS, dietary OBS, lifestyle OBS, and the 10-year ASCVD risk. The cohort study found that the OBS was inversely associated with all-cause (aHRs = 0.97, 95% CI = 0.96–0.99) and CVD (aHRs = 0.95, 95% CI = 0.93–0.98) mortality in individuals with high ASCVD risk. A significant linear correlation was observed between OBS, dietary OBS, lifestyle OBS, and all-cause and CVD mortality in participants with high ASCVD risk. Conclusion The findings indicate that OBS, OBS related to diet, and OBS related to lifestyle were significantly inversely correlated with the 10-year ASCVD risk. Adopting a healthy eating plan and making positive lifestyle choices that result in increased OBS levels can help lower the likelihood of all-cause and CVD mortality in individuals with high ASCVD risk.